ANALYSIS OF THE FINANCIAL PERFORMANCE ON THE BASIS OF THE PROFIT AND LOSS ACCOUNT, EXAMPLE SC DANONE PRODUCTION AND DISTRIBUTION OF FOOD PRODUCTS SRL BUCHAREST - ILIE RĂSCOLEAN; ILEANA- SORINA RAKOS (Annals of the University of Petrosani: Economics)
Through this article the authors intend to show that the summary accounting documents reflect the level of performance of an economic entity over a certain period of time, usually during a financial year. Unlike the balance sheet that presents the assets and liabilities of a company, the profit and loss account is a dynamic report that highlights the total flows of income and expenses in a given period. Regardless of the level of complexity of the profit and loss account it contains three important parts based on which an analysis of the financial situation of an economic entity can be made. Thus, the authors considered eloquent, the example of the company SCDanone PDPA Bucharest, a company with a strong reputation in the world, being the market leader of dairy products. The period taken into account is three years, respectively the years 2017 - 2019. The objective of the study is to show that, the analysis of the situation The profit and loss account is important for the financial manager, it shows practically the way in which the profit of the company is formed and the possible difficulties. financial from the level of the economic entity, as well as the reasons that were the basis of their appearance. Also, depending on the results obtained from the analysis, managers are able to make the best business decisions. The paper concludes with a brief presentation of the results of the study undertaken and of the conclusions obtained as a result of the research carried out.